Structure of hyperthermophilic β-glucosidase from Pyrococcus furiosus - Kado, Yuji (International Union of Crystallography, 2011)

(untitled)
Recombinant hyperthermophilic β-glucosidase from P. furiosus was crystallized. The crystal structure was solved to a resolution of 2.35 Å.